The association between blood pressure variability and renal damage in patients with primary aldosteronism - Siying Wu; Sen Li; Jing Huang; Jie Yu; Chaoping Wei; Lixia Wei; Shuangbei Zhu; Shanshan Chen; Meilan Chen; Jianling Li (The Journal of Clinical Hypertension, 2024)
Abstract This research examines the association between blood pressure variability (BPV) and renal damage in a cohort of 129 primary aldosteronism (PA) patients, employing ambulatory blood pressure monitoring (ABPM) for comparative analysis with individuals diagnosed with essential hypertension (EH). The study reveals that PA patients exhibited significantly elevated levels of cystatin C and urine microalbumin/creatinine ratio (UACR). Additionally, a higher prevalence of non‐dipping blood pressure patterns in PA patients suggests an increased risk of circadian blood pressure regulation disturbances. Notably, while most BPV indices were comparable between the two groups, the standard deviation of 24‐h weighted diastolic blood pressure was markedly lower in the PA cohort, distinguishing it as a unique variable. Through multiple linear regression analysis, the duration of hypertension, angiotensin II concentrations, and daytime systolic blood pressure standard deviation emerged as significant determinants of estimated glomerular filtration rate (eGFR) in PA patients. Furthermore, UACR was significantly influenced by variables including the 24‐h weighted standard deviation (wSD) of systolic BP, glycosylated hemoglobin levels, nocturnal systolic BP peaks, aldosterone‐renin ratio (ARR), and total cholesterol, with the most pronounced association observed with the 24‐h wSD of systolic BP (β = 0.383).The study also found significant correlations between the 24‐h wSD of systolic BP, ARR, HbA1c, serum potassium levels, and 24‐h urinary microalbumin, underscoring the critical role of the 24‐h wSD of systolic BP (β = 0.267). These findings underscore the imperative of an integrated management strategy for PA, addressing the intricate interconnections among metabolic abnormalities, blood pressure variability, and renal health outcomes.